THE GOOD GOVERNANCE BASE ADMINISTRATION OF NIWET TAWATBURI DISTRICT, ROI-ET PROVINCE - Thitatummo, Pra Raphin; Arunyawat, Sutthiphan (Journal of Graduate MCU KhonKaen Campus, 2020)
Research on administrative work according to the good governance principles of the Niwet Sub-district Municipality Thawat Buri District This time, Roi Et Province was conducted with a quantitative research methodology. Its objectives are 1) to study the implementation of the good governance of the personnel under the Niwet Subdistrict Municipality Thawat Buri District 2) Study the effectiveness of the work of the personnel under the Niwet Subdistrict Municipality Thawat Buri District 3) Study the relationship between good governance principles and operational effectiveness of personnel under the Niwet Subdistrict Municipality. Thawat Buri District 4) Study the guidelines for improving the effectiveness of the operation according to the good governance and the personnel of the Niwet Subdistrict Municipality. Thawat Buri District And 5) study the balanced organization management of personnel under the Niwet Sub-district Municipality. Thawat Buri District Roi Et Province The sample group consisted of administrators, members of the municipal council 65 municipal employees and employees were collected by using 5 Rating Scale questionnaire. Statistics used for data analysis were frequency, percentage, mean, standard deviation. And the Pearson product moment correlation coefficient. The results of the research showed that Compliance with the good governance principles of the personnel under the Niwes Sub-district Municipality Thawat Buri District Roi Et Province The overall picture is in the high level (= 3.67) and when considering each aspect, it is found that every aspect is in a high level, arranged from the highest to the lowest, namely the moral (= 3.71) the rule of law (= 3.70) the transparency principle ( = 3.69) Principles of participation (= 3.69) Responsibility principles (= 3.66) and Value principles (= 3.60) respectively Performance effectiveness of personnel under the Niwes Sub-district Municipality Thawat Buri District Roi Et Province The overall picture is in the high level (= 3.69). Personnel are responsible for their operations. To cooperate Help in their work group Caring for the people equally. Always produce excellent work. Develop methods of work that are always effective etc. Good governance principles correlate with the effectiveness of operations. Statistical significance that The significance level of 0.01 is based on the assumptions set. With a positive relationship at a medium level (r = .45). When considering each aspect, it was found that The practice of good governance in all aspects. Correlate with the effectiveness of the operation Statistical significance Based on the assumptions With a positive relationship at a medium level, including moral principles Principles of participation Transparency, moral principles, value principles, except for the principles of responsibility. There is a positive relationship at a low level. The guideline for improving the effectiveness of the operation according to the good governance principle is that executives and personnel must study the laws and regulations that are constantly changing. Adhere to the moral principles Create awareness in the performance of duties Adhering to good accuracy Disclosure and ready to be audited Giving people opportunities to participate in all areas, creating responsibility in the face of And establish righteousness in administration Budget should be allocated To be worth To benefit the organization development Balanced organization management of personnel under the Niwet Sub-district Municipality Thawat Buri District There are 4 aspects of Roi Et Province consisting of 1) the effectiveness according to the development plan of the municipality 2) the quality of service 3) the efficiency of government practice 4) the organization development